When It Comes to AI, Think Protopia, Not Dystopia or Utopia. - SHERMER, MICHAEL (Skeptic, 2024)
The article explores the potential risks associated with artificial intelligence (AI), particularly the views of AI dystopians like Eliezer Yudkowsky. It warns of the dangers of superhumanly smart AI, suggesting that without proper alignment and understanding, such AI could lead to catastrophic outcomes, including the extinction of humanity. It contrasts these dystopian views with AI utopians, who envision AI bringing about limitless prosperity and advancements.